Relações econômicas em uma fase de crescimento de novilhas com três graus de sangue, em Viçosa, Minas Gerais - de Lima, João Eustáquio; Teixeira Filho, Antônio Raphael; Dias Teixeira , Teotônio; Milagres, João Camilo (Revista Ceres, 2025)
This study deals wity economic analysis of experimental da- ta collected in an study of cattle feeding. Three groups of heifers of differing breads. High Grade Holstein, 3/4 Holstein Zebu and 1/4 Holstein Zebu were givem the same feed. Their feed consumption and weight were measured bi weekly throughout the experiment. The data collected were analysed with the use of production function concepts.